THE RELATIONSHIP BETWEEN TYPICALLY DEVELOPING SIBLINGS OF AUTISTIC CHILDREN AND THEIR ACADEMIC ACHIEVEMENT, SELF-CONCEPT, AND PSYCHOLOGICAL ADJUSTMENT - Dr. Aqeel Ahmad Khan; Gull Naz Khan; Muhammad Sajjad; Madiha Akram; Aamir Iqbal; Ravi Raja; Rabia Bashir; Allah Ditta (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objectives: The current study examines the academic, emotional, and psychological outcomes of usually developing siblings of children with autism. It was assumed that the siblings of autistic children would likewise have negative outcomes. Autistic children have higher levels of academic success, self-esteem, and psychological adjustment when compared to their typically developing siblings. Methods: The study employed a between-group design and utilized quantitative methods. The study had a grand total of 88 individuals. Out of the total participants, there were 22 children diagnosed with autism, 22 usually developing siblings, 22 moms, and 22 normal controls. All of them took part in the study together with their respective mothers. Path analysis, hierarchical regression, correlation coefficient, independent sample t test, and data were employed for data analysis. Results: Autistic children showed much poorer psychological adjustment and self-concept compared to their regularly developing siblings. Mothers with children who have autism experience elevated levels of stress in comparison to mothers whose children do not have autism. Individuals who have siblings with autism are at a higher risk of encountering psychological and emotional challenges, as well as behavioral and social issues. The psychological adaptation of siblings of autistic children is influenced by parental stress, rejection, and family discord. Path analysis reveals a significant impact of maternal depression and stress on the psychological adjustment, pro-social conduct, academic performance, and self-concept of siblings. Conclusion: The level of control exerted by one’s family has a significant impact on how one perceives oneself, while conflicts within the family have a considerable influence on one’s psychological well-being and tendency to engage in pro-social conduct. Taking into account the cultural context of Pakistan, researchers, mental health specialists, and doctors evaluate the importance of these findings.